The Development of HomeChef: A Recipe Finder Mobile App - BIN SAHARTANG, AHMAD SYUKRI; BINTI AB.AZIZ, RUHAYA (Applied Information Technology And Computer Science, 2024)
Traditional approaches often lead to uninspiring choices, inefficient ingredient use, and time-consuming recipe searches. Motivated by these issues, HomeChef, a groundbreaking Recipe Finder Mobile Application, addresses the prevalent challenge of meal planning and preparation faced by individuals. The HomeChef app adopts the Prototyping Model to streamline these processes. With modules like ingredient management, recipe discovery, and meal planning, HomeChef optimizes food utilization and simplifies meal planning. Incorporating advanced Search and Filtering algorithms enhances recipe import and modification. User acceptance testing confirms its effectiveness, making home cooking accessible and sustainable. Software such as Cloud Firestore Database and Flutter are used to develop the system. This study unveils an innovative solution to culinary challenges, promoting healthier and eco-conscious meal practices.